The Partner - John Grisham (UK Arrow Books, 1997)
A thriller on the international movement of dirty money. Its protagonist is an American lawyer who skips the country with $90 million belonging to crooks. They catch up with him in Brazil, torture him, but he does not know where the money is, his lawyer girlfriend is circulating it around the globe. Extradited to the U.S. to face various charges he is going to use the money to get off.
Keywords: Literature (3GdCOHs; General -- Fiction; Death, Apparent; Larceny -- Fiction